(3GdUjf aj GaQjbjG (B:s (3TQjc Ce efGaS (B/s - (3CdOf, cQjSs; (3GdeJdhKj, YKeGf LHGdj s ((3HjQhJ(B: s (3GdOGQ GdYQHjI ddYdhe fGTQhf(B, s, 2009)
(3SjGSI GdUjf GdLOjOI JLGg GaQjbjG, GdUjfjhf aj GaQjbjG (B: (3QCSeGdjhf, QGab Ce GfJgGRjhf, QOhO GdaYd GdZQHjI JLGg GdUjf h JhWjO GdYdGbI GdUjfjI GdGaQjbjIs
Keywords: (3EaQjbjG hGdUjf(B- (3GdEbJUGOs; (3GdUjf(B- (3GdEbJUGOs; (3GdUjf(B- (3GdYdGbGJ GdEbJUGOjI GdOhdjIs